Revolutions as disasters of misconceived political projects of social mutations - Mamali , Cătălin (Filozofia Publiczna i Edukacja Demokratyczna, 2021)
The study reviews the book You say you want a revolution? Radical idealism and its tragic consequences by D. Chirot (Princeton, Princeton University Press, 2020) and, at the same time, advances a viewpoint on social revolutions based on Thoreau’s imperative of the separation from evil. Why most social revolutions have dangerous and painful consequences while their promoters claim that the revolution will alleviate human suffering and will bring happiness? The study identifies more sources of the tragic consequences of revolutions than the radical idealism as suggested by Chirot. In contrast with the ideological, structural and individual violence of communist revolutions shaped by Marxist conception the study explores the value of Thoreauvian’s heuristic for the achievement of peaceful, non‑violent revolutionary changes. Self‑reliance i is assumed to be a vital engine of peaceful revolutionary changes.